Recolección y recopilación de información relacionada con las prácticas pre profesionales realizada por los estudiantes de la Universidad Politécnica Salesiana de noveno y décimo semestre de la carrera de Psicología en los espacios asignados dentro del Proyecto Salesiano Chicos de La Calle en la ciudad de Quito durante el periodo comprendido entre los años 2005 – 2017 - Cevallos Sáenz, Jonathan Stalin (2018)
The following work is a report on the systematization of all the available information related to the pre-professional practices carried out by the ninth and tenth-semester psychology students of the Salesian Polytechnic University in the Salesian Boys of the Street Project. The information found on the Practices in the Salesian project went through three stages: Collection, organization and systematization; that is, that all the information corresponding to the delimitation mentioned above was collected, organized and classified according to the results found and systematized both the information found and the work experience. This supposes not only a work of information collection, but that of forced way it will have to analyze the corresponding information and to know the dynamics that were presented on these. These results allow us to know how we have worked in recent years, see positive and negative points of this and allows us to make the corresponding conclusions and recommendations in order to optimize the work done in this space. Finally, an analysis is made based on the work of social psychology in this space and a vindication is made of this branch of work, which shows the importance of social psychology and the reason for this work.